The discount mechanism in the United States - GARVY, G. (PSL Quarterly Review, 2014)
<!--[if gte mso 9]> 72 1024x768 <![endif]--> In July 1968 the Federal Reserve Board released a broad-gauged study of the discount mechanism containing significant proposals for changes in existing arrangements for access to central bank credit at the initiative of member banks. The proposals, rather than representing a radical departure from past practises, are designed to reestablish the discount window in its traditional role as a temporary source of bank liquidity. The discount mechanism study represents one of the most ambitious efforts undertaken by the FED to explore ways for improving an important monetary tool at its disposal in light of past experience. The present article briefly reviews the important differences between the role of the discount mechanism in the United States and in the other leading countries, before discussing the scope and significance of the Discount Study and its recommendations. JEL: E51, E52, E58 <!--[if gte mso 9]> Normal 0 14 <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->